Transforming from Traditional to Smart Education in Nigeria: Challenges and Opportunities for Learning - CHUKWUEMEKA, Emeka Joshua; DOMINIC, Samaila; AKANBI, Kehinde Rasheedat; AREGBESOLA, Busayo Gbemisola (Ilorin Journal of Education, 2025)
This paper examines the transformation of Nigeria’s education system from traditional, teacher-centered methods to smart, technology-driven learning environments. The traditional Nigerian educational system, characterized by local methodologies and limited technological infrastructure, fails to foster essential 21st-century skills like critical thinking, creativity, and problem solving. The growing global emphasis on digital literacy and smart education presents Nigeria with an urgent need for reform to meet the demands of the evolving global workforce. Smart education leverages advanced technologies such as artificial intelligence (AI), the Internet of Things (IoT), and cloud computing to create interactive, personalized, and efficient learning experiences. Smart classrooms, in particular, offer collaborative and flexible learning opportunities, fostering innovation and creativity. Despite the potential benefits, the integration of smart education in Nigeria faces challenges, including inadequate infrastructure, insufficient teacher training, and the rigidity of existing curricula. However, successful implementation of smart education could bridge Nigeria’s technological gap and empower students with the skills needed to compete globally. This study critically analyzes the benefits and challenges of adopting smart education, comparing it with traditional methods, and highlights the importance of creating inclusive, high-quality learning environments that prepare students for the digital age. The study calls for comprehensive policy frameworks and strategic investments to facilitate this educational transformation, aligning Nigeria’s education system with global standards and ensuring its contribution to the country’s broader socio-economic development.